Analysis of Radiation Dose to the Shoulder by Treatment Technique and Correlation With Patient Reported Outcomes in Patients Receiving Regional Nodal Irradiation - Bazan, Jose G.; DiCostanzo, Dominic; Hock, Karen; Jhawar, Sachin; Kuhn, Karla; Lindsey, Kylee; Tedrick, Kayla; Healy, Erin; Beyer, Sasha; White, Julia R. (Frontiers in Oncology, 2021)
Background/Purpose Shoulder/arm morbidity is a late complication of breast cancer treatment with surgery and regional nodal irradiation (RNI). We set to analyze the impact of radiation technique [intensity modulated radiation therapy (IMRT) or 3D conformal radiation therapy (3DCRT)] on radiation dose to the shoulder with a hypothesis that IMRT use results in smaller volume of shoulder receiving radiation. We explored the relationship of treatment technique on long-term patient-reported outcomes using the quick disabilities of the arm, shoulder, and hand (q-DASH) questionnaire. Materials/Methods We identified patients treated with adjuvant RNI (50 Gy/25 fractions) from 2013 to 2018. We retrospectively contoured the shoulder organ-at-risk (OAR) from 2 cm above the ipsilateral supraclavicular (SCL) planning target volume (PTV) to the inferior SCL PTV slice and calculated the absolute volume of shoulder OAR receiving 5–50 Gy (V5–V50). We identified patients that completed a q-DASH questionnaire ≥6 months from the end of RNI. Results We included 410 RNI patients: 54% stage III, 72% mastectomy, 35% treated with IMRT. IMRT resulted in significant reductions in the shoulder OAR volume receiving 20–50 Gy vs. 3DCRT. In total, 82 patients completed the q-DASH. The mean (SD) q-DASH=25.4 (19.1) and tended to be lower with IMRT vs. 3DCRT: 19.6 (16.4) vs. 27.8 (19.8), p=0.078. Conclusion We found that IMRT reduces radiation dose to the shoulder and is associated with a trend toward reduced q-DASH scores ≥6 months post-RNI in a subset of our cohort. These results support prospective evaluation of IMRT as a technique to reduce shoulder morbidity in breast cancer patients receiving RNI.